2020
DOI: 10.5114/pedm.2020.93250
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diet quality, nutrient intake, and dietary behaviours in obese children compared to healthy children

Abstract: Assessment of diet quality, nutrient intake, and dietary behaviours in obese children compared to healthy children Ocena jakości diety, spożycia składników odżywczych i zachowań żywieniowych u dzieci otyłych w porównaniu z dziećmi zdrowymi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In general, previous research has identified obese children as being at a higher risk of cobalamin deficiency [40]. These findings are supported by multiple studies reporting malnutrition associated with overweight and obesity in children, due to poor dietary content, and repeated short-term restrictive diets combined with increased nutritional requirements, leading to vitamin and mineral deficiencies [41][42][43]. Since cobalamin and folate play a pivotal role in metabolism, special attention should be paid not only to calorie reduction but also to promoting a nutrientdense diet in overweight and obese children to ensure sufficient growth and development.…”
Section: Influence Of Bmimentioning
confidence: 83%
“…In general, previous research has identified obese children as being at a higher risk of cobalamin deficiency [40]. These findings are supported by multiple studies reporting malnutrition associated with overweight and obesity in children, due to poor dietary content, and repeated short-term restrictive diets combined with increased nutritional requirements, leading to vitamin and mineral deficiencies [41][42][43]. Since cobalamin and folate play a pivotal role in metabolism, special attention should be paid not only to calorie reduction but also to promoting a nutrientdense diet in overweight and obese children to ensure sufficient growth and development.…”
Section: Influence Of Bmimentioning
confidence: 83%
“…However, several studies have assessed that children with malnutrition related to overweight, obesity, and metabolic syndrome are at increased risk of mineral and vitamin deficiencies [ 88 , 89 ]. Hence, reduced vitamin B12 and folate serum levels may be caused by poor dietary content; short-term, repeated restricted diets; or increased requirements [ 11 , 89 ].…”
Section: Micronutrients Deficiency In Childhood Obesitymentioning
confidence: 99%